2008
DOI: 10.1002/anie.200800585
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (+)‐Oocydin A: Application of the Suzuki–Miyaura Cross‐Coupling of 1,1‐Dichloro‐1‐alkenes with 9‐Alkyl 9‐BBN

Abstract: Two sensitive fragments were coupled in the mild title reaction to create the Z‐chlorovinyl functionality of the target macrolide oocydin A (1; see scheme). Another highlight in the total synthesis of 1 was an efficient stereoselective Pd0‐catalyzed cyclization to form the highly substituted tetrahydrofuran ring. Bz=benzoyl, TBS=tert‐butyldimethylsilyl, MPM=4‐methoxyphenylmethyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 33 publications
0
37
0
1
Order By: Relevance
“…A onestep protection gave the 2,3-acetonide dimethyl ester, [20,21] which was then reduced [22] to provide diol 6. Mono protection of one alcohol with tBuMe 2 SiCl [23] followed by iodination [24] of the remaining hydroxy group gave 7 in an excellent 67 % overall yield over the four steps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A onestep protection gave the 2,3-acetonide dimethyl ester, [20,21] which was then reduced [22] to provide diol 6. Mono protection of one alcohol with tBuMe 2 SiCl [23] followed by iodination [24] of the remaining hydroxy group gave 7 in an excellent 67 % overall yield over the four steps.…”
Section: Resultsmentioning
confidence: 99%
“…Accurate masses were recorded on Mariner time-of-flight spectrometers. Compounds 6, [20][21][22] 7, [23,24] and 8 [24] were synthesized as described previously and spectroscopic data matched that of previously published spectra.…”
Section: Methodsmentioning
confidence: 99%
“…62 Later, Gandon and Roulland studied this reaction by DFT calculations. 63 The authors concluded that during the formation of a THF from a diol, the unreactive hydroxyl function controlled the stereochemical outcome of the reaction by complexing the palladium through the acetyl counteranion (Scheme 19).…”
Section: Scheme 18: Palladium Catalyzed Synthesis Of Thf From Phosphomentioning
confidence: 99%
“…77,78 The oxidation of a complex substrate bearing a primary alcohol has been described by Hirama and co-workers (Scheme 5). ROMPM, 114,115,118,183 ROBn, 80,90,104,106,110,124,191,192 ROTr, 180 ROMe, 94,101,107,113,192 RONPhth, 88 RON=CMe 2 , 88 ArOAllyl, 193 ArOMe, 108,130,131,192,194,195 ArOBn, 127,131 ArOTBS, 174 R 2 NBoc, 174,[194][195][196][197] 208 This IBX analogue generates only water during the oxidation, while DMP releases acetic acid. When DMP was applied the required keto ester was obtained in only 60%, with 40% of the starting lactone recovered (Scheme 6).…”
Section: 76mentioning
confidence: 99%